Use and Training in Ultrasound in the Emergency Room - Pinzón Vargas, Sandy; Pontificia Universidad Javeriana-Hospital Universitario de San Ignacio (Pontificia Universidad Javeriana, 2013)
Ultrasound has become a common practice in many emergency departments in the United States, which has generated most residency programs in emergency medicine, include ultrasound training within their curriculum. Emergency services has created the need for ultrasound use to allow rapid diagnosis of conditions that need to be immediately identified due to its high mortality, such as intra-abdominal hemorrhage in the context of the trauma patient, aortic aneurysm, and cardiac tamponade pneumothorax. Their application generates the opportunity for early diagnosis, prompt treatment, and reduction the patient’s stay in the emergency room. Besides implementation, avoids the need to transfer patients potentially unstable out of the area resuscitation, which can generate complications. Ultrasound has become a tool for performing procedures, such as vascular access, paracentesis, thoracentesis, etc. diminishing risk of possible complications that arise when these procedures are performed blindly